Progress in scale modeling, volume II selections from the International Symposia on Scale Modeling, ISSM VI (2009) and ISSM VII (2013) - Saito, Kozo 1950-; Ito, Akihiko; Nakamura, Yuji; Kuwana, Kazunori (Springer International Publishing, 2015)
This volume thoroughly covers scale modeling and serves as the definitive source of information on scale modeling as a powerful simplifying and clarifying tool used by scientists and engineers across many disciplines. The book elucidates techniques used when it would be too expensive, or too difficult, to test a system of interest in the field. Topics addressed in the current edition include scale modeling to study weather systems, diffusion of pollution in air or water, chemical process in 3-D turbulent flow, multiphase combustion, flame propagation, biological systems, behavior of materials at nano- and micro-scales, and many more. This is an ideal book for students, both graduate and undergraduate, as well as engineers and scientists interested in the latest developments in scale modeling. This book also: Enables readers to evaluate essential and salient aspects of profoundly complex systems, mechanisms, and phenomena at scale Offers engineers and designers a new point of view, liberating creative and innovative ideas and solutions Serves the widest range of readers across the engineering disciplines and in science and medicine.